2022
DOI: 10.1002/ajmg.a.63053
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of clinical exome sequencing in adulthood in medical genetics clinics

Abstract: Clinical exome sequencing (ES) is the most comprehensive genomic test to identify underlying genetic diseases in Canada. We performed this retrospective cohort study to investigate the diagnostic yield of clinical ES in adulthood. Inclusion criteria were: (1) Adult patients ≥18 years old; (2) Patients underwent clinical ES between January 1 and December 31, 2021; (3) Patients were seen in the Department of Medical Genetics. We reviewed patient charts. We applied American College of Medical Genetics and Genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…Similar diagnostic yields have been reported from neurogenetic clinics elsewhere, including 33% from a neurogenetics clinic in Israel, 21 27% in Argentina 22 and 30% in the United States 23 . However, lower diagnostic yields have been reported from other settings, including a diagnostic yield of 21% from exome sequencing for adolescents and adults with neurogenetic conditions in Australia, 6 19.5% from an adult general genetics clinic in Canada 24 and 17–19% from an unselected cohort referred to a medical genomics laboratory in the United States 25,26 . Although not directly comparable, the higher diagnostic rates observed in our and previous studies where MDT assessments took place prior to testing, compared with those reported by genomic laboratories, may reflect the additional benefit of an iterative MDT clinical assessment and/or multiple testing pathways.…”
Section: Discussionsupporting
confidence: 62%
“…Similar diagnostic yields have been reported from neurogenetic clinics elsewhere, including 33% from a neurogenetics clinic in Israel, 21 27% in Argentina 22 and 30% in the United States 23 . However, lower diagnostic yields have been reported from other settings, including a diagnostic yield of 21% from exome sequencing for adolescents and adults with neurogenetic conditions in Australia, 6 19.5% from an adult general genetics clinic in Canada 24 and 17–19% from an unselected cohort referred to a medical genomics laboratory in the United States 25,26 . Although not directly comparable, the higher diagnostic rates observed in our and previous studies where MDT assessments took place prior to testing, compared with those reported by genomic laboratories, may reflect the additional benefit of an iterative MDT clinical assessment and/or multiple testing pathways.…”
Section: Discussionsupporting
confidence: 62%
“…In a study of whole genome sequencing in 100 generally healthy pa1ents aged 40-65 years in the primary care seong, Vassy et al discovered a new gene1c diagnosis in 22%, 16 although many pa1ents exhibited only minimal symptoms of their diagnosis. In other studies of adult pa1ents with suspicion for a gene1c diagnosis, 14,15,[17][18][19] the diagnos1c rate of exome sequencing has been reported to range from 14-29% -lower than that observed in the pediatric popula1on, 25 but high enough to demonstrate the u1lity of broad gene1c tes1ng approaches in adults. The diagnos1c rate of 24% that we report in our study is in keeping with these previous reports, despite the fact that the popula1on we examined was not specifically selected for suspicion of gene1c disease.…”
Section: Discussionmentioning
confidence: 94%
“…many patients exhibited only minimal symptoms of their diagnosis. In other studies of adult patients with suspicion for a genetic diagnosis,14,15,[17][18][19] …”
mentioning
confidence: 99%
“…Almost 100 individuals with suspected or confirmed MED13L haploinsufficiency syndrome have been reported to date [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. According to the DECIPHER database, there are additional pathogenic MED13L deletions and duplications.…”
Section: Discussionmentioning
confidence: 99%